Mapping the Landscape of Islamic Human Capital: Research Trends, Emerging Gaps, and Prospect - Hadyantari, Faizatu Almas; Almas, Lauditta Iftinan; Hutami, Dina (Yayasan Rahmat Islamiyah, 2025)
Human resource development in the context of Islamic economics is a key focus in efforts to improve the quality of human resources by Islamic principles. Through an analysis of 194 documents from the Scopus database (2017-2024), this study maps trends, thematic patterns, and research gaps through keyword co-occurrence analysis using VOSviewer software. The findings of this study propose a novel contribution through a matrix that serves as an initial conceptual framework for formulating an integrated human resource model based on Islamic values. Six clusters of keywords—human capital intellectual capital, socio-demographics, Islamic institutions, Muslim country context, sustainable finance, and social capital entrepreneurship—are recommended as potential areas for research novelty.